2015
DOI: 10.1073/pnas.1511134112
|View full text |Cite
|
Sign up to set email alerts
|

Universal spectrum of normal modes in low-temperature glasses

Abstract: We report an analytical study of the vibrational spectrum of the simplest model of jamming, the soft perceptron. We identify two distinct classes of soft modes. The first kind of modes are related to isostaticity and appear only in the close vicinity of the jamming transition. The second kind of modes instead are present everywhere in the glass phase and are related to the hierarchical structure of the potential energy landscape. Our results highlight the universality of the spectrum of normal modes in disorde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
258
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(290 citation statements)
references
References 50 publications
(173 reference statements)
28
258
4
Order By: Relevance
“…This new Gardner transition is completely disconnected from the jamming point.) This re-entrant behaviour is in agreement with very recent studies on the spectrum of harmonic vibrations of elastic sphere glasses 22,32 . In summary, we have shown that, by cooling, amorphous solids undergo the same transition towards a marginal glass state as found for hard spheres 12 .…”
supporting
confidence: 92%
See 2 more Smart Citations
“…This new Gardner transition is completely disconnected from the jamming point.) This re-entrant behaviour is in agreement with very recent studies on the spectrum of harmonic vibrations of elastic sphere glasses 22,32 . In summary, we have shown that, by cooling, amorphous solids undergo the same transition towards a marginal glass state as found for hard spheres 12 .…”
supporting
confidence: 92%
“…In summary, we have shown that, by cooling, amorphous solids undergo the same transition towards a marginal glass state as found for hard spheres 12 . The marginality of this new solid phase is related to the presence of long-range correlations and soft modes 10,22 . We can now turn to our main concern, which is the change in the elastic properties of the solid approaching the Gardner transition.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The exact solution for the vibrational modes around jamming presents a vast excess of low-frequency modes compared with the Debye model for solids (a so-called Boson peak) (75). The low-frequency limit of the density of states does not vanish as in the Debye model but tends to a constant (89,93,94,95,96).…”
Section: Mean-field Jamming Criticalitymentioning
confidence: 93%
“…The physical origin of this effect has no fully satisfying explanation. The universality of the phenomenon is also thought to apply far beyond structural glasses (124,75). Second, renormalization group analysis of these effects have yet to be fully developed (86).…”
Section: Ongoing and Future Directionsmentioning
confidence: 99%